Strategies to Foster Pluralism Awareness through Islamic Religious Education at Bumi Damai Foundation Yogyakarta - Nashrullah, Muhammad Iqbal; Kholis, Nur; Mukaromah, Siti; Basyir, Kunawi (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
This article aims to analyze the strategies used in cultivating pluralism awareness through Islamic Education at Bumi Damai Foundation, Yogyakarta. This research uses qualitative research methods with a case study approach. Interviews were conducted with caregivers, heads of institutions, and teachers. All interviews are recorded and then transcripts of interview results are provided. Data analysis uses 3 stages: data reduction, data display, and drawing/verifying data conclusions. This study found that the Bumi Damai Foundation in implementing a strategy to foster pluralism awareness through Islamic Education implements several programs, namely: the tahfidz program with emphasis on memorization of the context of pluralism contained in the Qur’an, Da’wah Al-Muhibbin studying several areas from different cultures and religions, applying the motto Hubbul Wathon Minal Iman, visits and social services in several non-Muslim places of worship, and emphasized memorizing and deepening the contents of Asmaul Husna. This research contributes to scarcity studies that uncover strategies and methods for cultivating awareness of pluralism within Social Welfare Institutions. Similar research is appropriate to uncover strategies of Islamic forms of education used to foster awareness of pluralism in social institutions.